Scanning electron microscopy evaluation of dentin ultrastructure after surface demineralization - Kuntze, Morgane; Mendes Souza, Beatriz; Schmidt, Tamer; Almeida, Josiane; Bortoluzzi, Eduardo; Felippe, Wilson (Journal of conservative dentistry, 2020)
Context: Knowledge about dentin microstructure is essential for execution of clinical procedures which require adhesion of materials to dentin. Aims: To evaluate by scanning electron microscopy (SEM) the dentin ultrastructure after demineralization with 6 M and 12 M hydrochloric acid (HCl). Subjects and Methods: Twenty dentin segments were immersed in fixative solution and dehydrated in ethanol. After 24 h, segments were randomly divided into 2 groups (n = 10), demineralized with 6 M HCl (G6M) and 12 M HCl (G12M), and prepared for SEM analysis. Statistical Analysis Used: Based on photomicrographs and chemical composition (energy dispersive X-ray spectroscopy) of dentin, a descriptive analysis was conducted. Results: G6M samples revealed a demineralized surface with peritubular dentin exposure and small magnification of the dentinal tubules openings. The intertubular dentin was partially demineralized. Demineralization of G12M samples was more aggressive and at different depths, promoting erosion and "detachment" of dentin layers. Peritubular dentin was observed on the dentin surface. There was a large magnification of the dentinal tubules openings. In both groups, tubular structures showed a similar chemical composition to the intertubular dentin. Lamina limitans was not observed. Conclusions: Dentin demineralization is dependent on the HCl molarity and promotes exposure of peritubular dentin.